2017
DOI: 10.1002/hed.24759
|View full text |Cite
|
Sign up to set email alerts
|

Expression of AKR1B10 as an independent marker for poor prognosis in human oral squamous cell carcinoma

Abstract: AKR1B10 overexpression is an independent poor prognostic biomarker for OSCC. AKR1B10 inhibitors may be promising in clinical trials against OSCC. © 2017 Wiley Periodicals, Inc. Head Neck 39: 1327-1332, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 37 publications
(117 reference statements)
4
23
0
Order By: Relevance
“…In this study, we confirmed that high expression of AKR1B10 was a common feature (62%; Table ) and was a valuable prognostic marker for OSCC (Table ). Our results were consistent with the study by Ko et al in that high level of AKR1B10 expression is associated with poor prognosis in OSCC . A following study has indicated that the level of AKR1B10 in saliva could be an indicator for screening high‐risk patients and monitoring the progression of OSCC .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, we confirmed that high expression of AKR1B10 was a common feature (62%; Table ) and was a valuable prognostic marker for OSCC (Table ). Our results were consistent with the study by Ko et al in that high level of AKR1B10 expression is associated with poor prognosis in OSCC . A following study has indicated that the level of AKR1B10 in saliva could be an indicator for screening high‐risk patients and monitoring the progression of OSCC .…”
Section: Discussionsupporting
confidence: 93%
“…Our results were consistent with the study by Ko et al in that high level of AKR1B10 expression is associated with poor prognosis in OSCC. 18 A following study has indicated that the level of AKR1B10 in saliva could be an indicator for screening highrisk patients and monitoring the progression of OSCC. 21 Here, our study further demonstrated that high expression of AKR1B10 was correlated with increased incidence of tumor recurrence ( Table 2) and short disease-free survival ( Figure 2D to F).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7] Elevated expression of AKR1B10 is found in nonsmall cell lung, hepatocellular, nasopharyngeal, cervical, pancreatic, and breast carcinomas. 14 AKR1B10 is a secretory protein. Recently, we demonstrated that a higher mean AKR1B10 labeling score, as assessed using immunochemical staining, is significantly associated with an advanced TNM classification and shorter survival in patients with OSCC.…”
Section: Introductionmentioning
confidence: 99%